Changes in mRNA Degradation Efficiencies under Varying Conditions Are Regulated by Multiple Determinants in Arabidopsis thaliana. (8th December 2020) - Ueno, Daishin; Mikami, Maki; Yamasaki, Shotaro; Kaneko, Miho; Mukuta, Takafumi; Demura, Taku; Kato, Ko
Abstract: Multiple mechanisms are involved in gene expression, with mRNA degradation being critical for the control of mRNA accumulation. In plants, although some trans-acting factors and motif sequences have been identified in deadenylation-dependent mRNA degradation, endonucleolytic cleavage-dependent mRNA degradation has not been studied in detail. Previously, we developed truncated RNA-end sequencing (TREseq) in Arabidopsis thaliana and detected G-rich sequence motifs around 5′ degradation intermediates. However, it remained to be elucidated whether degradation efficiencies of 5′ degradation intermediates in A. thaliana vary among growth conditions and developmental stages. To address this issue, we conducted TREseq of cultured cells under heat stress and at three developmental stages (seedlings, expanding leaves and expanded leaves) and compared 5′ degradation intermediates data among the samples. Although some 5′ degradation intermediates had almost identical degradation efficiencies, others differed among conditions. We focused on the genes and sites whose degradation efficiencies differed. Changes in degradation efficiencies at the gene and site levels revealed an effect on mRNA accumulation in all comparisons. These changes in degradation efficiencies involved multiple determinants, including mRNA length and translation efficiency. These results suggest that several determinants govern the efficiency of mRNA degradation in plants, helping the organism to adapt to varying conditions by controlling mRNA accumulation.